2011
DOI: 10.3727/096368910x543385
|View full text |Cite
|
Sign up to set email alerts
|

Human Amnion Epithelial Cells Prevent Bleomycin-Induced Lung Injury and Preserve Lung Function

Abstract: Human amnion epithelial cells (hAECs) have attracted recent attention as a promising source of cells for regenerative therapies, with reports that cells derived from human term amnion possess multipotent differentiation ability, low immunogenicity, and anti-inflammatory properties. Specifically, in animal models of lung disease characterized by significant loss of lung tissue secondary to chronic inflammation and fibrosis, the transplantation of hAECs has been shown to reduce both inflammation and subsequent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
171
3
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(193 citation statements)
references
References 49 publications
14
171
3
4
Order By: Relevance
“…Rather, we suggest that the hAECs mised mice have shown that both hAECs (31) and amniotic fluid-derived cells (6) are able to integrate into the primarily exert their effects by reducing acute inflammation, both leukocyte infiltration and cytokine responses, host epithelium and differentiate in vivo into lung epithelial cells following bleomycin lung injury (6), we and thereby mitigating subsequent pulmonary fibrosis. A wide array of inflammatory and fibrotic signaling have not been able to show this in immune competent mice in either a previous study (33) or in this current pathways are activated by bleomycin, including key players in lung injury such as TGF-β (2), the inflammastudy. Acknowledging that FACS analysis, one of the approaches we use for cell detection, excludes dead cells some (12,30,46), and inflammatory cytokines such as…”
Section: Effect Of Haec Supernatant On Macrophage Migration In Vitromentioning
confidence: 99%
See 4 more Smart Citations
“…Rather, we suggest that the hAECs mised mice have shown that both hAECs (31) and amniotic fluid-derived cells (6) are able to integrate into the primarily exert their effects by reducing acute inflammation, both leukocyte infiltration and cytokine responses, host epithelium and differentiate in vivo into lung epithelial cells following bleomycin lung injury (6), we and thereby mitigating subsequent pulmonary fibrosis. A wide array of inflammatory and fibrotic signaling have not been able to show this in immune competent mice in either a previous study (33) or in this current pathways are activated by bleomycin, including key players in lung injury such as TGF-β (2), the inflammastudy. Acknowledging that FACS analysis, one of the approaches we use for cell detection, excludes dead cells some (12,30,46), and inflammatory cytokines such as…”
Section: Effect Of Haec Supernatant On Macrophage Migration In Vitromentioning
confidence: 99%
“…With this in mind, there has been recent interest which hAECs exert their effects in this model of lung injury remain uncertain. In particular, it is not clear in the reparative/regenerative potential of cell-based whether hAECs exert their effects via differentiating and fibrosis maximum at day 14 following bleomycin treatment (33). Body weight, core temperature, and into lung epithelial cells in vivo, as we have shown occurs in immune-compromised mice (31), or whether basal lung function were recorded prior to commencement of experiments and at days 3, 7, and 14. the principle mechanism is via modulation of the host response to injury.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations